Spatially and intertemporally efficient waste management: The costs of interstate flow control - Eduardo Ley; Molly K. Macauley; Stephen W. Salant (Fondazione Eni Enrico Mattei (FEEM), 1998)
We examine the problem of the intertemporal allocation of the solid waste of cities within the United States to spatially distributed landfills and incinerators, taking into account that capacity at existing and potential landfills is scarce. Amendments to the Solid Waste Disposal Act have been proposed to restrict waste flows between states by means of quotas and surcharges. We assess the aggregate surplus loss (and its regional distribution) resulting from proposed policies. In addition, we find that limitations on the size of shipments to any one state will have the perverse effect of substantially increasing interstate waste shipments as states export smaller volumes to more destinations.
Keywords: C6; D6; Q3; 330; Solid waste; efficiency; Abfallpolitik; Intertemporale Allokation; Mülldeponie; Räumliche Verteilung; Wirtschaftliche Effizienz; Kommunale Abfallwirtschaft; USA